(untitled) - Haag, Stephen (Boston, MA., 2004)
The I-Series : Computing concepts is built entirely around one theme-productivity. White providing your students with the most current and relevant information technology content, The I-Series: computing concepts couches every single topic within the context your student's productivity: Can boxed elements, student learning outcomes, practically speaking boxed elements
Keywords: Electronic data processing